Aflatoxin B1 adsorption/desorption dynamics in the presence of Lactobacillus rhamnosus RC007 in a gastrointestinal tract-simulated model - Fochesato, Analía Silvia (2019)
Aims: (i) To determine the aflatoxin B1 (AFB1) adsorption and desorption dynamics in the presence of Lactobacillus rhamnosus RC007 under simulated transit of AFB1 at each gastrointestinal tract (GIT—saliva, stomach and intestine) stage consecutively and then, separately, (ii) to study the ability of L. rhamnosus RC007 to biotransform AFB1 as a strategy that complements the adsorption process. Methods and Results: The AFB1 adsorption and desorption assay simulating the GIT passage of AFB1 (93·89 ng g−1) in the presence of L. rhamnosus RC007 (108 CFU per ml) was conducted. Moreover, lactic acid production was determined. Results demonstrated that predominant environmental conditions in salivary solution induced a low AFB1 adsorption, while the transit through the gastric solution and intestinal solution allowed high percentages of adsorption and did not generate significant AFB1 desorption. Conclusions: The AFB1 adsorption and desorption dynamics in the presence of L. rhamnosus RC007 was favoured by gastric and intestinal environment. Significance and Impact of the Study: The knowledge of the adsorption dynamics of AFB1 with a micro-organism of interest will allow predicting its behaviour at each stage of the GIT.